Weight lifting can facilitate appreciative comprehension for museum exhibits - Yamada, Yuki; Harada, Shinya; Choi, Wonje; Fujino, Rika; Tokunaga, Akinobu; Gao, YueYun; Miura, Kayo (Frontiers in Psychology, 2014)
Appreciation of exhibits in a museum can be equated to a virtual experience of lives in the contexts originally surrounding the exhibits. Here we focus on the importance of weight information, and hence tested whether experiencing a weight during museum exhibit appreciation affects the beholders’ satisfaction and recognition memory for the exhibits. An experiment was performed at a museum exhibiting skeletal preparations of animals. We used nine preparations and prepared four weight stimuli as weight cues in accordance with the actual weight of four of the preparations: Remaining five preparations was displayed without weight stimuli. In the cued condition, participants were asked to lift up the weight stimuli during their observation of the four exhibits. In the uncued condition, participants observed the exhibits without touching the weight stimuli. After observation of the exhibits, the participants responded to a questionnaire that measured their impressions of the exhibits and the museum, and performed a recognition test on the exhibits. Results showed that memory performance was better and viewing duration was longer with weight lifting instruction than without instruction. A factor analysis on the questionnaires revealed four factors (likeability, contentment, value, and quality). A path analysis showed indirect effects of viewing duration on memory performance and willingness-to-pay for the museum appreciation through the impression factors. Our findings provide insight into a new interactive exhibition that enables long appreciation producing positive effects on visitors’ impression, memory, and value estimation for exhibits.